2025 ALUMINUM COATING USING CARBON POWDER WITH TEMPERATURE OF 600°C, 700°C AND 800°C USING HEAT TREATMENT METHOD - Antonius Prisma Jalu Permana; Nereus Tugur Redationo; Emilianus Chris Welafubun (Mechanical, Energy and Material (METAL), 2023)
Aluminum coating in Indonesia is one of the business fields that has experienced an increase in development and rapid progress starting from the type of coating used to produce coatings that also vary. The purpose of this study was to determine the hot temperatures of 600°C, 700°C and 800°C in the aluminum coating process uses carbon powder and determines the effective hardness values ​​at temperatures of 600°C, 700°C, and 800°C. Test result hardness shows that the highest average hardness value is at a temperature of 600°C of 68.6 Hv and the lowest average hardness value is at a temperature of 800°C which is equal to 51.7 Hv